Modes of transillumination of the dense plasma layer via electromagnetic beam - Mykhailenko, B.R.; Anisimov, I.O. (Вопросы атомной науки и техники, 2021)
Interaction of the powerful electromagnetic ray of the limited radius with a dense plasma layer was studied via computer simulation using the PIConGPU software package in 3D geometry. The characteristic modes of channel formation in the barrier (namely laminar and turbulent) are described. Turbulent mode can be associated with the fast transillumination, observed in laboratory experiments. The channel formation time as a function of the incident beam power and the plasma layer density is studied. Information transparency is also observed at the third harmonic of the incident wave. Шляхом комп’ютерного моделювання за допомогою пакета PIConGPU у тривимірній геометрії досліджено взаємодію потужного електромагнітного променю обмеженого радіусу з плоским шаром щільної плазми. Описано характерні режими формування каналу в бар’єрі – турбулентний та ламінарний. Турбулентний режим можна пов’язати з так званим швидким просвітленням, що спостерігалося в лабораторних експериментах. Досліджено залежність часу формування каналу в залежності від потужності падаючого променя та густини плазмового шару. Спостерігалося також перенесення сигналу через бар’єр на третій гармоніці падаючої хвилі. Путем компьютерного моделирования с применением программного пакета PIConGPU в трехмерной геометрии исследовано взаимодействие мощного электромагнитного пучка ограниченного радиуса с плоским слоем плотной плазмы. Описаны характерные режимы формирования канала в барьере – турбулентный и ламинарный. Турбулентный режим можно связать с так называемым быстрым просветлением, которое наблюдалось в лабораторных экспериментах. Исследована зависимость времени формирования канала в зависимости от мощности падающего луча и плотности плазменного слоя. Также наблюдался перенос сигнала через барьер на третьей гармонике падающей волны.